Co-organiser - Koureas, Gabriel (My University, 2026)
'The Ground Beneath our Feet: Four Artists from Cyprus Discuss Archaeology and Contemporary Art', co-organised with Elena Parpa and Christina Lambrou, the Cyprus High Commission-Cultural Section and the British Museum under the auspices of the High Commissioner for the Republic of Cyprus Euripides L. Evriviades to celebrate the Cyprus National Day